Pengaruh Disiplin Kerja dan Lingkungan Kerja Non Fisik terhadap Kinerja Karyawan pada PT Paro Profesional Tangerang Selatan - Sudarso, Eko (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The background of this research stems from the need to improve employee performance through internal organizational factors, particularly work discipline and non-physical work environment. The purpose of this study is to determine the influence of work discipline and non-physical work environment on employee performance at PT Paro Profesional, both partially and simultaneously. This study employs a quantitative method. The population consists of 85 respondents, and the sampling technique used is saturated sampling, resulting in a total sample of 85 respondents. Data analysis includes validity and reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of the study show that work discipline and non-physical work environment have a positive and significant influence on employee performance, both individually and together. This indicates that enhancing employee discipline and improving non-physical work conditions such as interpersonal relationships and a supportive work atmosphere can contribute to better performance. The strong relationship between these variables highlights the importance of management in fostering a culture of discipline and creating a conducive work environment. The implication is that the organization should prioritize strengthening work discipline and enhancing non-physical aspects of the work environment to boost employee productivity.